Effect of tart cherry juice on recovery and next day performance in well-trained Water Polo players. Issue 1 (December 2016) - McCormick, Rachel; Peeling, Peter; Binnie, Martyn; Dawson, Brian; Sim, Marc
Abstract Background Tart Montmorency cherries contain high concentrations of phytochemicals and anthocyanins, which have recently been linked to improved athletic recovery and subsequent performance. To date however, previous work reporting promising results has focused on land-based endurance sports, with any potential benefits to team sports remaining unknown. As such, this investigation set-out to examine the effect of supplemental tart cherry juice (CJ) on recovery and next day athletic performance in highly-trained water-based team sport athletes over seven days. Methods In a randomised, double-blind, repeated measures, crossover design, nine male Water Polo athletes were supplemented with CJ or a placebo equivalent (PLA) for six consecutive days. Prior to, and at the completion of the supplementation period, water-based performance testing was conducted. On day 6, participants also undertook a fatiguing simulated team game activity. Venous blood samples were collected (Pre-exercise: day 1, 6 and 7; Post-exercise: day 6) to investigate markers of inflammation [Interleukin-6 (IL-6); C-reactive protein (CRP)] and oxidative stress [Uric Acid (UA); F2-Isoprostane (F2-IsoP)]. A daily diary was also completed (total quality of recovery, delayed onset muscle soreness) as a measure of perceptual recovery. Results In both conditions, day 6 post-exercise IL-6 was significantly higher than pre-exercise and day 7 (p  < 0.05); CRP was greater on day 7 as compared to day 6 pre- and post-exercise (p  < 0.05); F2-IsoP was significantly lower on day 7 as compared to day 1 and day 6 (p  < 0.05); UA remained unchanged (p  > 0.05). No differences were found for any performance or recovery measures. Conclusions The lack of difference observed in the blood markers between groups may reflect the intermittent, non-weight bearing demands of Water Polo, with such activity possibly unable to create a substantial inflammatory response or oxidative stress (over 7 days) to impede performance; thereby negating any potential beneficial effects associated with CJ supplementation. Trial registration This trial was registered with the Australian and New Zealand Clinical Trials Registry (ANZCTR). Registration number:ACTRN12616001080415 . Date registered: 11/08/2016, retrospectively registered.